Going Beyond the Visible in Type 2 Diabetes Mellitus: Defense Mechanisms and Their Associations With Depression and Health-Related Quality of Life - Martino, Gabriella; Caputo, Andrea; Bellone, Federica; Quattropani, Maria C.; Vicario, Carmelo M. (Frontiers in Psychology, 2020)
Introduction Clinical psychological features may impact a person’s aptitude to deal with chronic diseases, leading to emotional distress, suffering, and a worse perceived quality of life (QoL). Chronic diseases are largely represented, and their incidence is constantly increasing all over the world. Type 2 Diabetes Mellitus (T2DM) is one of the most common chronic diseases and it is very difficult to manage, demanding long term self-management, which improves the perceived QoL. The aim of this study was to explore defense mechanisms, depression, QoL, time since diagnosis, and metabolic control in T2DM patients. Methods 51 patients with T2DM were assessed through a psychodiagnostic battery: Beck Depression Inventory-II, the 36-Item Short Form Health Survey, including indexes of Physical and Mental Component Summary and the Defense Mechanisms Inventory. Times since DM diagnosis and glycated hemoglobin values were detected. Results Participants were mainly female (62.74%), with a mean age of 66.1 years. T2M time since diagnosis was 11.77 years (SD = 7.1). Mild depression was detected (with an overall score between 13 and 19). Projection was significantly associated with higher depression and with lower physical well-being; Principalization was negatively associated with depression and positively with both physical and mental well-being. Turning Against Self correlated positively with physical well-being and negatively with mental well-being. Reversal was associated with lower depression and higher mental well-being. A negative high correlation emerged between depression and mental well-being. Finally, a significant relationship was found between Projection and higher time since diagnosis (r = 0.31, p < 0.05). Conclusion The correlations between defense mechanisms, depression and health-related QoL highlight the potential personification and protagonization, which may increase over time due to the illness intrusiveness and worsening of diabetes symptoms. The positive association between defensive strategies and well-being measures should be cautiously considered.